2017
DOI: 10.3892/mmr.2017.6205
|View full text |Cite
|
Sign up to set email alerts
|

Metformin suppresses the expression of Sonic hedgehog in gastric cancer cells

Abstract: Abstract. The traditional anti-diabetic drug, metformin, has been found to have anticancer effects. The Sonic hedgehog (Shh) signaling pathway is involved in the on cogenesis of gastric cancer. The aim of the present study was to investigate whether metformin has an effect on the Shh signaling pathway in gastric cancer cells. HGC-27 and MKN-45 human gastric cancer cells were treated with metformin at different concentrations and for different durations. Subsequently the mRNA and protein levels of Shh, Smoothen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…GLI protein expression in tissue samples were examined by western blotting and IHC. In 8 of the 10 cases, both methods revealed that the expression of all GLI proteins was significantly increased in HCC tissues when compared with normal adjacent tissues ( Figures 1A, B ), a finding which is consistent with those for other cancer types, including gastric, colorectal, lung, breast, and pancreatic cancer (Kasper et al, 2006; Lauth and Toftgard, 2007; Song et al, 2017; Didiasova et al, 2018).…”
Section: Resultssupporting
confidence: 81%
“…GLI protein expression in tissue samples were examined by western blotting and IHC. In 8 of the 10 cases, both methods revealed that the expression of all GLI proteins was significantly increased in HCC tissues when compared with normal adjacent tissues ( Figures 1A, B ), a finding which is consistent with those for other cancer types, including gastric, colorectal, lung, breast, and pancreatic cancer (Kasper et al, 2006; Lauth and Toftgard, 2007; Song et al, 2017; Didiasova et al, 2018).…”
Section: Resultssupporting
confidence: 81%
“… 85 A follow-up study led by the same group showed that both protein and mRNA levels of Shh and Gli 1, Gli2, Gli3 were decreased by metformin in two GC cell lines in a dose- and time-dependent manner. 86 …”
Section: Metformin’s Anti-tumor Effects On Gastric Cancermentioning
confidence: 99%
“…Metformin was reported to directly inhibit mTOR signaling by inactivating Rag GTPases (158), or inducing cell cycle arrest through REDD1, a negative regulator of mTOR (159). Furthermore, several other intracellular effectors were reported to be modulated by metformin treatment to reduce cell proliferation, including, among others, the VEGF/PI3K/Akt pathway (160) in prostate cancer cells, Sonic hedgehog (Shh) signaling pathway in gastric cancer cells (161), inactivation of p38 MAPK and activation of ERK3 (both effects leading to inhibition of mTORC1, in which AMPK was only partially involved) in intrahepatic cholangiocarcinoma cells (162), reversal of the activation of ERK1/2 in ovarian cancer cells (163), inhibition of CLIC1 in gallbladder cancer cells (164); metformin also counterbalanced the overactivation of Notch1/Hes1 signaling observed in colorectal cancer patients (165), and induced apoptosis via the up-regulation of adenosine A1 receptor in human colorectal cancer cells (166). Other putative mechanisms of metformin anti-tumor activity involve the reduced RANKL (167) or caveolin 1 (168) expression in breast CSCs, and HIF-1α gene expression in oral squamous cell carcinoma cell lines, which caused inhibition of cell proliferation and migration (169).…”
Section: Development Of Pharmacological Tools To Target Clic1 Activitmentioning
confidence: 99%